Application of Activity Based Costing for Palm Oil Plantation - Chak, Wen Zheng; Abu, Mohd Yazid (Penerbit UMP, 2019)
Malaysia is one of the largest producers and exporters of palm oil in the world, accounting for 11% of the world's oils & fats production and 27% of the export trade of oils & fats. Oil palm tree will start bearing fruits after 30 months of field planting and will continue to be productive for the next 20 to 30 years. Thus, a proper costing method is very important in order to have a clear picture about its profit loss and gain for the next 20 to 30 years. Subsequently, Traditional Cost Accounting (TCA) which the manufacturing overhead are driven by the production volume are being applied. The inaccurate cost estimation will lead the management hard to do decisions making. The aim of this work is to apply the Activity Based Costing (ABC) as a method of cost estimation for the palm oil plantation. The ABC has been applied to analyse the costing of every activities involved in the palm oil plantation. Under the support of actual cost information and proper cost drivers, accurate profitability will able to be calculated. Accurate profitability is the most important factor for the management to identify on the money that process in order to maintain rapid but sustainable growth. Therefore, ABC system will provide actual cost information and proper cost drivers for each of the activities being involved. Thus, it makes the company’s profitability more accurate.